ADAPTASI ETNIS MELAYU TAMIANG DALAM DINAMIKA SOSIAL DAN CULTURE MASYARAKAT ACEH - Fariadi, Dedi; Fasya, Teuku Kemal; Yunanda, Rizki; Yusmalinda, Yusmalinda (Program Studi Sosiologi Universitas Malikussaleh, 2023)
This research examines the presence of the Tamiang Malay ethnic group in Aceh, especially in the classification known as host ethnics, which is decreasing in existence amidst the rampant migration of other tribes, especially the Javanese who inhabit plantation areas in Aceh Tamiang. The purpose of this study is to provide a description of the construction of Tamiang Malay culture in the social and cultural dynamics of the Acehnese people. This study uses qualitative methods by collecting observational data, interviews, and documentation studies. The results of the study show that the existence of the Tamiang Malay ethnicity is divided into two Malay community groups that differ in the use of accents in the pronunciation of the language. The Malay tribe who inhabit the upstream part of the Tamiang daily dialect uses the letter